CIVIL SOCIALIZATION AS AN INDICATOR AND INTEGRATOR OF FORMATION OF CIVIC IDENTITY IN THE CONTEXT OF NATIONAL POLICY OF THE RUSSIAN FEDERATION - V. N. Konovalov (Современная наука и инновации, 2022)
The article focuses on "civil socialization" as an indicator and integrator of the development of civil identity. Civil socialization is explored as a process of achieving a "universal legal civil society" or institutionalizing a social contract based on "ownership"